Campus polls see shift towards pro-govt groups: strong message: 'Pro-Aspirasi' factions win big on student welfare platform - Lai, Adrian; Anwar, Zafira (New Straits Times, 2015)
FOR the last few term, the majority of student representative councils at public universities were dominated by the 'pro-Mahasiswa' group seen as suppotive of the opposition.